A alma-camaleão e sua plasticidade:: dualismos platônicos no Fédon - Cornelli, Gabriele (Revista Archai, 2015)
Abstract: This paper aims to address the problem of the separation between body and soul in Plato’s Phaedo, in search of both its ontological features and moral consequences. Apart from the traditional approach and use of dialogue as a literary and philosophical milestone for all body-soul dualisms in the history of philosophy, I believe that two ways of understanding this separation are outlined in the dialogue. The first one would indicate a moral separation, regarding what a philosopher should take care of: philosophers would be able to cure of the soul, but not of the body. A different way to address this separation between body and soul is the one I would like to consider as an ontological separation: the soul is so independent from the body that is declared to survive after its death. Although both concepts of this separation could seem pretty familiar, due to the success they had throughout the history of Platonism until today, the duplicity of meanings expressed by the Platonic passages carries on an irrevocable ambiguity. The aim of this paper is to propose, however, is a quite different solution for resolve this ambiguity. My suggestion is that we should pay the proper attention to the ontological and epistemological ductility of the soul. Bostock (1986, p. 119 @Phd. 79c), called it the chameleon-like traits of the soul, enabling the soul to assume bodily features to meet the sensible world. Separation between body and soul, rather than an ontological, seems to need the contribution of a permanent epistemological and moral effort of the soul. Keywords: Plato, Soul, Phaedo, Affinity argument.